Radiographic Nuances in Allergic Fungal Rhinosinusitis. Issue 3 (May 2019) - Rowan, Nicholas R.; Janz, Tyler A.; Schlosser, Rodney J.; Soler, Zachary M.
Background: Allergic fungal rhinosinusitis (AFRS) is characterized by higher revision endoscopic sinus surgery (ESS) rates and unique radiographic features when compared to chronic rhinosinusitis with nasal polyposis (CRSwNP) or chronic rhinosinusitis without nasal polyposis (CRSsNP). Objective: We hypothesized that an increased frequency of concha bullosa in AFRS or other radiographic nuances might allow for accumulation of allergic mucin and contribute to increased ESS revision rates. Methods: A retrospective cohort study was performed. Patient diagnosis (AFRS, CRSwNP, and CRSsNP), basic demographics, and prior ESS rates were collected. Results: A total of 210 consecutive patients were included (AFRS = 70, CRSwNP = 70, and CRSsNP = 70). Pediatric AFRS patients had more unilateral disease (38.1% vs 4.4%; P = .007) and anterior ethmoid skull base erosion (23.8% vs 6.7%; P = .047) than adult AFRS patients. AFRS patients were more likely to be younger (24.9 ± 10.1 years vs 45.6 ± 14.4 years vs 48.7 ± 18.2 years; P < .001), African American (70% vs 14.3% vs 11.4%; P < .001), and have undergone prior ESS (54.3% vs 45.7% vs 31.4%; P = .02) than CRSwNP or CRSsNP patients. Concha bullosa were more prevalent in AFRS patients than CRSwNP or CRSsNP patients across the population (42.9%, 18.6%, and 14.3%; P < .001) and in the setting of no previous surgery (53.1%, 31.6%, and 16.7%; P < .001). Conclusion: In this cohort, pediatric AFRS patients had more unilateral disease and anterior ethmoid skull base erosion. Concha bullosa prevalence was significantly higher in AFRS as compared to those with CRSwNP or CRSsNP, despite prior ESS. Surgeons should consider concha bullosa as a potential anatomical subsite to harbor recurrent or residual disease.